The Development of Curriculum Enhancing Basic Moral for Students Lower Secondary School of Pariyattitham School in Ubonratchatani Province under the National Office of Buddhism: - (Adoon Chaneewong), Prakru Patara Panyanuyud (Dhammathas Academic Journal, 2023)
This Research was the objectives: 1) to study the current situation and the problems in the development of Enhancing Curriculum basic morality, 2) to construct the Enhancing Curriculum basic morality, 3) to study the experimental results the Enhancing Curriculum basic morality, 4) to study the satisfaction of students towards the Enhancing Curriculum basic morality. The research takes the research and development model, with 4 phases: Phase 1: Study of current conditions, problems, 3 methods: (1) Inquire about the current situation, problems (2) Interviews with experts, (3) Study visits in schools with the concept good practices in education management to enhancing basic morals. Phase 2: The curriculum creation and instruction manual of Curriculum. Phase 3: Experimental use of the enhancing curriculum basic morality. Phase 4: Assessment of student satisfaction with the Enhancing Curriculum basic morality. The statistics used in the research were basic statistics: Percentage, Mean, Standard Deviation, and t-test for dependent sample statistics. The results was the research as follows: 1. At present, the development of the basic morality optional curriculum was at a high level and Moderate problem. 2. The basic morality optional curriculum were consists of 6 elements, namely: principles, learning outcomes, the structure of unit learning, media, and learning resources; measurement and evaluation. Course quality and course manual have the overall appropriateness at the highest level. 3. The experimental results of the Basic Moral optional Curriculum found that, (1) The students' basic morality after learning were higher than before learning at the statistical significance level of .05. (2) The post-test score was higher than before the test at the statistical significantly .05 level. (3) Efficiency of the Basic Moral Empowerment Program (E1/E2) was 80.90/82.13. 4. The results of the study were the students satisfaction with the basic morality optional curriculum. The students were found that satisfied at a high level.